HUBUNGAN POLA ASUH DENGAN PRESTASI BELAJAR SISWA KELAS III SD NEGERI 187 PEKANBARU - Siti Aisyah; Otang Kurniaman; Mahmud Alpusari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Based on the results of interviews conducted by researchers at one of the homeroom teacher of SDN 187 Pekanbaru III obtained information that there are students who received less attention from both parents, as parents are paying less attention when his study time at home. This resulted in the child being lazy to do their homework from teacher when in the school. In addition, children often want to obtain a high learning outcomes, but in a way that is not good, for example cheating. It is very negative impact on children's development. Because of achieving satisfactory progress in addition to learning is also supported by the application of appropriate parenting, as if in applying the wrong upbringing will adversely affect personal attitudes and children. The purpose of this study was to determine the relationship between parenting and student’s academic achievement class III SDN students 187 Pekanbaru. This type of research is a quantitative research study population was all students of class III Elementary School Pekanbaru, amounting to 136 187 students. While the sample is saturated samples. Because it does not receive permission from the guardian class IIIb, the authors use two classes only as samples, namely classes IIIa and IIIc classes totaling 92 students, consisting of 53 male students and 39 female students. Data collection methods used were questionnaires transform and measure patterns of parenting and documentation for record of achievement students drawn from rapot value. The results showed that the correlation (r) of -0.048 and tcount smaller than ttable or -0.4629 <1.9866 at the significant level of 5%, so that it can be concluded that there is no relationship between parenting and academic achievement of students.Keywords: Parenting, academic achievement